Enhancing Social and Emotional Learning (SEL) Competencies among Education Students through the "Share a Book, Wake a Thought (SABWAT)" Activity - Angela Napa; Edward Babasa; Efsica Maranan; Arceli Gilera; Judith Asistin (Philippine Association of Institutions for Research, Inc., 2022)
The holistic development of every learner is one vital aim of schools. Thus, the College of Education of the University of Batangas maintains and enhances students' intellectual, physical and socio-emotional growth and development through developmentally-appropriate activities such as the Share a Book Wake a Thought (SABWAT) project. This research intended to enhance the social and emotional learning competencies of the student-donors of the books and eventually improve the ways the SABWAT activity would be handled in the next years. It utilized the descriptive research design with a self-constructed questionnaire as the main data gathering tool based on the Collaborative for Academic, Social and Emotional Learning (CASEL) Frameworks. It also used focus group discussion to verify the information gathered. Using stratified random sampling, the researchers selected 111 out of 235 enrolled students in the College of Education. The researchers used descriptive statistics such as mean and standard deviation. The findings revealed that the Education students, after being involved in the SABWAT activity, gained social awareness, self-awareness, responsible decision making, relationship skills, and self-management skills; the manifested application of these competencies in life. Major issues and challenges were the limited number of books donated, the small number of students being involved in the actual donation day, and the lack of information about the activity. The proposed SABWAT improvement plan aims to address the issues and challenges like the aforementioned. It is also intended to improve the SEL competencies of students through the various activities relative to SABWAT.